Hermatomyces pyriformis sp. nov., a novel dematiaceous hyphomycete (Hermatomycetaceae, Pleosporales) associated with medicinal plants in Yunnan Province, China - Du, Hong-Zhi; Liu, Ning-Guo; Cheewangkoon, Ratchadawan; Liu, Jian-Kui (Phytotaxa, 2024)
During investigations of hyphomycetous fungi from medicinal plants in Yunnan Province, China, a novel species of Hermatomyces was discovered. Hermatomyces pyriformis is introduced based on morphology and phylogenetic analyses of combined LSU, ITS, tef1-α and rpb2 sequence data. This fungus is characterized by having sporodochial conidiomata and determinate, hyaline, pyriform conidiogenous cells bearing brown, globose to subglobose or ellipsoidal, muriform lenticular conidia with dark brown center and brown peripheral cells. Phylogenetic results indicated that two isolates of H. pyriformis represent a distinct lineage and can be recognized as a new species. A detailed description and illustration are provided for the new species.